Biological evaluation of integrin α3β1-targeted 68Ga-labeled HEVNPs in HCT 116 colorectal tumor-bearing mice - Lambidis, Elisavet; Chen, Chun-Chieh; Lumen, Dave; Sánchez, Ana Isabel Fraguas; Sarparanta, Mirkka; Cheng, R. Holland; Airaksinen, Anu J. (European journal of pharmaceutical sciences, 2023)
•Simple functionalization of the targeted-HEVNPs, HEVNP-LXY30, with DOTA.•[68Ga]Ga-DOTA-HEVNP-LXY30 production in high efficiency and excellent purity.•Comparison of targeting capability toward murine breast & human colon cancer cells.•Highly sufficient targeting toward integrin α3β1-expressing human colon tumor cells.•Modest targeting capability toward HCT 116 tumor-bearing mouse model. Integrins are cell surface receptors involved in multiple functions vital for cellular proliferation. Various tumor cells overexpress αβ-integrins, making them ideal biomarkers for diagnostic imaging and tumor-targeted drug delivery. LXY30 is a peptide that can specifically recognize and interact with the integrin α3β1, a molecule overexpressed in breast, ovarian and colorectal cancer. Hepatitis E virus nanoparticles (HEVNPs) are virus-like particles that have been investigated as drug delivery agents for the targeted delivery of nucleic acids and small proteins. HEVNPs can be a theranostic platform for monitoring and evaluating tumor-targeted therapies if tagged with a suitable diagnostic marker. Herein, we describe the radiolabeling and biological evaluation of integrin α3β1-targeted HEVNPs. HEVNPs were conjugated with DOTA and radiolabeled with gallium-68 (t1/2 = 67.7 min), a short-lived positron emitter used in positron emission tomography (PET). The synthesized [68Ga]Ga-DOTA-HEVNPs were used to evaluate the efficacy of conjugated LXY30 peptide to improve HEVNPs binding and internalization to integrin α3β1 expressing human colorectal HCT 116 cells. In vivo tumor accumulation of [68Ga]Ga-DOTA-HEVNP-LXY30 was evaluated in HCT 116 colorectal tumor-bearing mice. [68Ga]Ga-DOTA-HEVNP-LXY30 and non-targeted [68Ga]Ga-DOTA-HEVNP were radiolabeled with radiochemical yields (RCY) of 67.9 ± 3.3% and 73.7 ± 9.8%, respectively. [68Ga]Ga-DOTA-HEVNP-LXY30 exhibited significantly higher internalization in HCT 116 cells than the non-targeted [68Ga]Ga-DOTA-HEVNPs (21.0 ± 0.7% vs. 10.5 ± 0.3% at 3 h, ***P<0.0001). After intravenous administration to mice, accumulation of [68Ga]Ga-DOTA-HEVNP-LXY30 to HCT 116 xenograft tumors was at its highest rate of 0.8 ± 0.4%ID/g at 60 min. [68Ga]Ga-DOTA-HEVNP-LXY30 accumulated mainly in the liver and spleen (39.8 ± 13.0%%ID/g and 24.6 ± 24.1%ID/g, respectively). Despite the low targeting efficiency in vivo, we demonstrated that [68Ga]Ga-DOTA-HEVNP is a promising diagnostic platform for quantitative analysis of HEVNP distribution in vivo. This nanosystem can be utilized in future studies assessing the success of further engineered HEVNP structures with optimized targeting efficiency in vivo. [Display omitted]